Cartel: teoria econômica e prática antitruste no Brasil - Flores, Gustavo Abrahão (2008)
The present work aims to analyze and comment the performance of the Administrative Council for Economic Defence (CADE), through the survey and summary of the conducting votes of the decisions pronounced for the autarchy, in cases already judged, referring to the behavior of cartel formation, in Brazil, standing out the elements, used indications and arguments, or for the conviction of the Represented ones, or filling of the process. However, such analysis, it will be made to the light of the existing economic theory on the strategies and oligopoly coordination, collusive models, tacit agreement, theory of the games, of the international jurisprudence and interpretations of the law of free market defense (Law 8.884/99). The main issue, it is not to answer if the pronounced decision was made right or makes a mistake, for the other hand, to allow to evaluate where measured, the economic theories and the jurisprudence are used, and if that are used coherently.